DYNAMICS OF URINARY TRACT INFECTIONS IN EARLY CHILDHOOD DURING ACUTE RESPIRATORY VIRAL INFECTION - Egamberdiev Sardorbek Muxammadiso ugli (Journal of Applied Science and Social Science, 2026)
In the structure of morbidity among pediatric patients, urinary system infections (USIs) rank second after acute respiratory viral infections (ARVIs). In children during the first three years of life, USIs occur more frequently than acute respiratory infections . The relevance of the problem of developing USIs against the background of ARVIs is determined by their high prevalence and the risk of severe complications in the urinary system (US), including chronic kidney disease (CKD), as well as the complexity of developing specific antiviral therapy in children, which is associated with etiological heterogeneity, high contagiousness of pathogens, and variability of viral antigenic properties . ARVIs in early childhood contribute to heightened immune responses and provoke superimposed bacterial infections, including the development of pyelonephritis and infections of the distal urinary tract.